Devising a technology for manufacturing hollow cast steel structures with composite and reinforced non-metallic functional filler - Shinsky, Oleg; Kvasnytska, Iuliia; Shalevska, Inna; Kaliuzhnyi, Pavlo; Neima, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the structure of hollow steel modules filled with various types of functional materials, as well as the technology of their production using lost foam casting. Computer simulation of hydrodynamic and heat-mass exchange processes and solidification was carried out to establish the laws and prerequisites for designing state-of-the-art hollow cast structures and to devise their production technology. The study investigated the influence of reinforced steel elements and reinforcement directly from the liquid alloy of the shell on the peculiarities of hydrodynamic, heat-mass transfer processes, and solidification during the production of hollow steel structures with functional fillers. It has been determined that the presence of polystyrene membranes in the functional filler for subsequent reinforcement from the liquid phase of the shell metal affects the hydrodynamics of filling the casting. In the thin channels formed in the filler, the metal flow rate increases from 2 m/s to 8 m/s in the upper channels, and from 3 m/s to 12 m/s in the lower channels, which is associated with an increase in metallostatic pressure. The presence of metal reinforcement in the functional filler and the reinforcement of the functional material from the liquid phase of the shell metal accelerates the heating of the non-metallic filler by 1.2–1.4 and 1.4–1.8 times, respectively. Reinforcement also helps increase the maximum heating temperature of the functional filler by 200–300 °C, which creates better conditions for its sintering. The grades of steels for their use as a matrix alloy in the production of hollow cast castings were determined; their structure and physical-mechanical properties were studied. The recommended modes of heat treatment of low-alloy steel to obtain the required properties have been determined. The study reported here is a theoretical prerequisite for verification in the manufacture of experimental cast hollow structures with metallic and non-metallic reinforcing phase